ABOUT THE BORROWING VICARIOUS MATERIAL IN SCIENCE AND IN EDUCATIONAL PROCESS (DISCUSSION) - Stanislav A. Lipski (Высшее образование в России)
The question about measures to counteract the borrowing vicarious material forscientific and educational work has not yet received proper discussion on the background of the problems associated with the unified state examination, the transition to two-tier system of higher education (bachelor - master) entering its final stage, and the reform of the Academies of Sciences (they caused a discussion in the scientific and teaching circles). The journalists, officials in the field of science and education and, finally, those who carry out suchan audit (advertising themselves) more vividly give their view on this topic. But there are somecontroversial points in this question, such as the difference in approaches to the scientific, educational and teaching and methodical materials; the existence of sufficient legal grounds; the optimality of the existing mechanism and others. Ignoring these issues will cause considerable damage to higher education and even greater losses to science.